How do you solve 5( u - 1) = 7u + 5- 5( - 2u - 1)?

2 Answers
Mar 9, 2018

u=-5/4

Explanation:

(5u-1)=7u+5-5(-2u-1)
5u-5=7u+5+10u+5
5u-5=17u+10
-15=12u
-15/12=u
u=-5/4

Mar 9, 2018

u = -(5)/(4)

Explanation:

5(u−1)=7u+5−5(−2u−1)    Solve for u

1) Clear the parentheses by distributing the 5 and the -5
After you have distributed, you will get this:
5u−5=7u+5+10u + 5

2) Combine like terms
After you have combined 7u with 10u, and 5 with the other 5, you will have this:
5u - 5 = 17u + 10

3) Subtract 5u from both sides to get the u terms together
Once you subtract, you will have this:
- 5 = 12u + 10

4) Subtract 10 from both sides to isolate the 12u term
- 15 = 12u

5) Divide both sides by 12 to isolate u
-(15)/(12) = u

6) Reduce the fraction to lowest terms
-(5)/(4) = u

Answer:
u = -(5)/(4)

Check

Sub in -(5)/(4) in the place of u in the original equation

This check is not worth the trouble it would take to do it.
You shouldn't waste your valuable time on this check.

If the answer is wrong, so be it.

Instead, why not take your dog outside for a run?